2014
DOI: 10.2169/internalmedicine.53.1174
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathological Findings of Four Cases of Pure Influenza Virus A Pneumonia

Abstract: Objective The purpose of this study was to perform clinicopathological evaluations of patients with pure influenza A virus pneumonia. Methods We performed clinicopathological analyses of four cases of pure influenza A virus pneumonia. Patients Among the four cases, three were caused by the pandemic (H1N1) 2009 virus. Three patients were analyzed during autopsy, and one underwent transbronchial lung biopsy. Results We suggest that the interval between influenza virus A pneumonia onset and our analysis affected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 26 publications
0
15
0
Order By: Relevance
“…Patients infected with IAV commonly have alveolar hemorrhage, and this is a complication of influenza pneumonia, particularly with the H1N1 strain [13,[45][46][47][48][49][50]. Importantly, retrospective studies have shown an association between alveolar hemorrhages and increased mortality [51,52].…”
Section: Discussionmentioning
confidence: 99%
“…Patients infected with IAV commonly have alveolar hemorrhage, and this is a complication of influenza pneumonia, particularly with the H1N1 strain [13,[45][46][47][48][49][50]. Importantly, retrospective studies have shown an association between alveolar hemorrhages and increased mortality [51,52].…”
Section: Discussionmentioning
confidence: 99%
“…Viral infection due to influenza, respiratory syncytial virus, and some coronavirus can lead to diffuse alveolar damage (DAD) and hemorrhage [24][25][26][27][28][29]. DAD begins with an acute or exudative phase, wherein fibrin is deposited within the airways preventing air exchange.…”
Section: Mechanisms Of Carv-mediated Allograft Dysfunctionmentioning
confidence: 99%
“…DAD begins with an acute or exudative phase, wherein fibrin is deposited within the airways preventing air exchange. Epithelial cell damage may then follow, leading to deposition of a hyaline membrane [29]. If these depositions are not cleared, an organizing phase of DAD develops with proliferation of smooth muscle cells and promotion of immature alveolar type II cells [29], followed by deposition of collagen and ultimately fibrosis.…”
Section: Mechanisms Of Carv-mediated Allograft Dysfunctionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, HMs in DAD have usually been found in clinical acute respiratory distress syndrome, [3][4][5] acute exacerbation of usual interstitial pneumonia (UIP), 6 or rheumatoid arthritis-associated interstitial pneumonia, viral 7 and/ or bacterial pneumonia, and in infected lungs in malignant diseases, including leukemic cell infiltration in the lung and other kinds of pulmonary or extrapulmonary cancers. 1 Recently, DAD was categorized into 2 groups: primary (infection) and secondary (chemotherapy or druginduced).…”
Section: Introductionmentioning
confidence: 99%